Placental Chorionic Cyst Fluid Has Prothrombotic Properties and Differs From Amniotic Fluid. (July 2019) - Stolla, Moritz; Refaai, Majed A; Conley, Grace; Spinelli, Sherry; Casey, Ann; Katerji, Hani; McRae, Hannah L; Blumberg, Neil; Phipps, Richard; Metlay, Leon A; Katzman, Philip J
Introduction: Chorionic cysts of the chorion laeve, fetal chorionic plate, septum, and free membranes have been associated with placental hypoxia, but they have no clear clinical significance. Although immunohistochemistry has identified fibronectin and collagen IV in cyst fluid, the contents have yet to be fully characterized. Methods: Placental chorionic cysts (N = 10) were sampled by fluid extraction and hemotoxylin and eosin-stained sections. Amniotic fluid samples (N = 8) were obtained from pregnant women who had cytogenetic evaluation. The content of the cysts was tested for thrombogenicity using thromboelastography. The cyst content was tested by Luminex multiplex and ELISA assays and for known prothrombotic and proinflammatory factors. Results: We identified cysts, especially those in the chorionic plate, adjacent to intervillous thrombi with apparent cyst rupture. Thromboelastography revealed a significantly shorter R time compared to whole blood control samples. Concentration of creatinine, α-fetoprotein, and surfactant D in the cyst fluid differed significantly from amniotic fluid. Cyst fluids had a significantly higher expression of all prothrombotic and some proinflammatory factors. Discussion: Our data provide the first evidence that chorionic cyst fluid is prothrombotic and different from amniotic fluid. The association of ruptured cysts with adjacent thrombi and the prothrombotic properties of cyst fluid suggest a causal relationship; however, further studies are needed.